SISTEM REKOMENDASI PADA PENJUALAN ELEKTRONIK MENGGUNAKAN METODE COLLABORATIVE FILTERING - Donny Susianto; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Recommendation system on electronic sales using collaborative filtering method is an application that can organize and inform products from electronics and recommend items based on similarities between users who have purchased products. Software development methodology using the waterfall method to the problems that arise in the product can not be found, customers do not get other similar product recommendations. By utilizing technology that is a recommendation system that can recommend products to customers. One method that can be used to provide a collaborative filtering method. This method can make it easier to provide electronic product recommendations by summing up the rating or choice of a product, finding user profiles/ patterns by looking at the history of ratings given by users, and generating a new recommendation. The Output of this system in the form of product recommendations that aim to help buyers choose the goods to be purchased, with the recommendation system is expected to reduce confusion in choosing products.